2010
DOI: 10.1021/ol902761a
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of 3-Aryloctahydroindoles and Application in a Formal Synthesis of (−)-Pancracine

Abstract: A stereoselective synthesis of 3-aryloctahydroindoles from enantiomerically enriched gamma-nitroketones has been developed. Reduction of imines derived form the nitroketones provides the trans-fused octhaydroindole motif selectively. The cis-octahydroindole skeleton is accessible by an invertive cyclization strategy involving a diastereomerically pure nitromesylate intermediate. This approach was employed in the synthesis of an advanced intermediate to (-)-pancracine. The gamma-nitroketone starting materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…55 As mentioned, the diaryl prolinol silyl ethers, general catalysts for aldehyde, do not work in the case of ketones because of the steric constraint of the requisite transition state. A good 89% ee and >19 : 1 dr was obtained using catalyst 89.…”
Section: Enamine Catalysismentioning
confidence: 99%
“…55 As mentioned, the diaryl prolinol silyl ethers, general catalysts for aldehyde, do not work in the case of ketones because of the steric constraint of the requisite transition state. A good 89% ee and >19 : 1 dr was obtained using catalyst 89.…”
Section: Enamine Catalysismentioning
confidence: 99%
“…Most of the asymmetric approaches known for the synthesis of montanine alkaloids are mainly based on chiral-pool strategies except for two recent reports on the formal synthesis of pancracine [17,18] based on organocatalytic approaches. The asymmetric 1,3-dipolar cycloaddition of azomethine ylides to a variety of alkenes has emerged as one of the most powerful strategies for the construction of enantiopure pyrrolidine ring systems.…”
Section: Development Of a Chiral Auxiliary Based Asymmetric 13-dipoamentioning
confidence: 99%
“…Overman, [11] Pearson, [12] Ikeda, [13] Sha, [14] Banwell, [15] Chang, [16] Hashimoto [17] and Pansare [18] and their co-workers all used precursors of type 9 in their respective elaborations of these alkaloids. However, in all these strategies, the syntheses were elaborated from a precursor having the desired stereochemistry at C-4a and C-11a and relative disposition of the methylene bridge of 8, which involved its construction in a stepwise manner.…”
Section: Introductionmentioning
confidence: 99%
“…It was envisaged that the development of a general method for the synthesis of chiral octahydroindoles bearing a non-functional group at their 2-position would provide a facile access to a broad range of chiral analogues that could exhibit potentially interesting biologically activities. Pansare et al [5] reported the stereoselective synthesis of 3-aryl-A C H T U N G T R E N N U N G octahydroindoles from g-nitro ketones via the organocatalytic Michael reaction of cyclohexanone with bmonosubstituted nitroolefins [Scheme 1, Eq. (1)].…”
mentioning
confidence: 99%
“…Nitroolefins bearing a variety of different electron-donating and electron-withdrawing substituents on their phenyl ring behaved as suitable substrates for the asymmetric Michael addition with cyclohexanone. High enantioselectivities (94 to > 99% ee) were achieved in all cases with good diastereoselectivities (84:16-94:6 dr) and yields (67-93%) ( Table 2, entries [1][2][3][4][5][6][7][8]. The position of the substituent appeared to have a significant influence on the yield (73-85%) and diastereoselectivity (88:12-94:6 dr) of the transformation, although the effect of the substituent on the enantioselectivity was only minor (94 to > 99% ee) ( Table 2, entries 4-6).…”
mentioning
confidence: 99%